The Influence of Children's Learning on Science (CLIS) Model on Student Learning Outcomes Integrated Thematics on Class IV Sd - Desi Indriyani; Desyandri Desyandri (Postgraduate School, Universitas Negeri Padang, 2019)
This study aims to determine the existence of a significant effect on student learning outcomes using the Children Learning In Science (CLIS) model on Class IV integrated thematic learning at SD Negeri 52 Parupuk Tabing. This type of research is an experimental study with Quasi Exsperimental design, with a non equivalent control group design. The sample technique used was purposive sampling technique with a sample consisting of two classes, namely the IVA class experimental class using the CLIS model which amounted to 24 students and class IVB control class using a scientific approach totaling 24 students. The results of the study with the t-test show that the average value of the class using the CLIS model is 76.25 and the class using the scientific approach is 71.5. Obtained results of tcount 1.8524> 1.67356 ttable at the 0.05 significance level. Thus it can be concluded that there is a significant influence on the use of the Children Learning In Science (CLIS) model on student learning outcomes in integrated thematic learning in grade IV SD.